Social Media and Peacebuilding
XV, 192 p. 15 illus., 6 illus. in color.
Keywords: This book makes a novel contribution to the literature by examining the intersection of social media, conflict and peacebuilding. It challenges traditional state-centric and Eurocentric approaches to international relations and peace and conflict studies by examining the role of social media in peacebuilding beyond a simplistic tech-solutionist versus tech-skeptical duality. The book explains why the impact of social media on peacebuilding is complex and depends on the political context and strategies of the actors involved in it. It uses an interdisciplinary lens to explore the potential and limitations of social media in peacebuilding, thereby contributing to a theoretical and empirical understanding of the role of digital technology in shaping conflict and promoting peace. Chapter “Fighting Hate Speech on Social Media: The Challenge of “Deep Work” in Digital Peacebuilding” is available open access under a Creative Commons Attribution BY 4.0 International license via link.springer.com. Anna Reuss is Lecturer and Researcher at the Chair of International Politics and Conflict Studies, University of the Bundeswehr Munich. At the Centre for Digitalisation and Technology Research of the German Armed Forces, she studies the potential of digitalisation in conflicts and its influence on peacebuilding. Stephan Stetter is Professor of International Politics and Conflict Studies at the University of the Bundeswehr Munich. His research focuses on theories of world society and global modernity in relation to international politics, as well as politics and society in the Middle East. He was editor of the leading German international relations journal Zeitschrift für Internationale Beziehungen.